SOA Algorithm for Secure Data Encryption and Decryption: A New Random Key-Based Encryption Method - Abu Irzayzah, Samyrah; Aljalali , Osamah; Aml Altirban; Rem Arebi (AlQalam Journal of Medical and Applied Sciences, 2025)
In this paper, we present the SOA algorithm, a novel approach to secure data encryption and decryption. The SOA algorithm is based on matrix-based operations and uses a unique method to divide text into blocks represented by matrices. Each block is encrypted using a randomly generated block key and a corresponding key matrix, ensuring that each block has a unique encryption. The encryption process combines block keys, key matrices, and fixed matrices to convert plaintext blocks into encrypted data. The decryption process uses the same block keys and includes a special matrix generated from the block key, fixed matrix, and identity matrix, allowing for accurate recovery of the original text. The SOA algorithm is characterized by its use of random keys for each block, with the addition of fixed matrices, ensuring a high level of security and resistance to attacks. This approach, based on random keys and complexity of key computations, provides a flexible, efficient, and mathematically powerful framework for modern data encryption and decryption, making it a promising way to secure sensitive information in various applications.